Obesity and leptin in breast cancer angiogenesis - Lagarde, Courtney B.; Thapa, Kapil; Cullen, Nicole M.; Hawes, Mackenzie L.; Salim, Khudeja; Benz, Megan C.; Dietrich, Sophie R.; Burow, Brandon E.; Bunnell, Bruce A.; Martin, Elizabeth C.; Collins-Burow, Bridgette M.; Lynch, Ronald M.; et al. (Frontiers in Endocrinology, 2024)
At the time of breast cancer diagnosis, most patients meet the diagnostic criteria to be classified as obese or overweight. This can significantly impact patient outcome: breast cancer patients with obesity (body mass index > 30) have a poorer prognosis compared to patients with a lean BMI. Obesity is associated with hyperleptinemia, and leptin is a well-established driver of metastasis in breast cancer. However, the effect of hyperleptinemia on angiogenesis in breast cancer is less well-known. Angiogenesis is an important process in breast cancer because it is essential for tumor growth beyond 1mm3 in size as well as cancer cell circulation and metastasis. This review investigates the role of leptin in regulating angiogenesis, specifically within the context of breast cancer and the associated tumor microenvironment in obese patients.